2017
DOI: 10.1186/s12879-017-2785-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antimicrobial resistant Escherichia coli from patients with suspected urinary tract infection in primary care, Denmark

Abstract: Background Escherichia coli is the most common pathogen causing Urinary Tract Infections (UTI). Data from the current National Surveillance program in Denmark (DANMAP) may not accurately represent the prevalence of resistant E. coli in primary care, because only urine samples from complicated cases may be forwarded to the microbiological departments at hospitals for diagnostic examination. The aim of this study was to assess the prevalence of resistant E. coli to the most commonly used antimicrobial agents in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 25 publications
5
24
0
1
Order By: Relevance
“…5 Previous studies of community-onset UTIs (CO-UTI) in several mainland European countries found that E. coli were the most commonly isolated uropathogen, accounting for over half of all isolates (53.3-76.7%). [6][7][8] The incidence of CO-UTI in the UK is difficult to determine since such infections are not reportable and most are diagnosed and treated in a primary care setting, with diagnosis often based solely upon patient symptoms rather than a positive urine culture. CO-UTI are most often treated empirically and subsequently local epidemiological data is useful for informing treatment choice.…”
Section: Introductionmentioning
confidence: 99%
“…5 Previous studies of community-onset UTIs (CO-UTI) in several mainland European countries found that E. coli were the most commonly isolated uropathogen, accounting for over half of all isolates (53.3-76.7%). [6][7][8] The incidence of CO-UTI in the UK is difficult to determine since such infections are not reportable and most are diagnosed and treated in a primary care setting, with diagnosis often based solely upon patient symptoms rather than a positive urine culture. CO-UTI are most often treated empirically and subsequently local epidemiological data is useful for informing treatment choice.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria such as Escherichia coli and Staphylococcus aureus are important agents of urinary tract infections [1][2][3][4]. Both bacteria are frequently detected in patients with indwelling urinary tract devices [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The most common pathogen, Escherichia coli, is from Enterobacteriaceae family with a prevalence of 75%-90%. Other common pathogens are Klebsiella pneumoniae, Proteus mirabilis and Staphylococcus saprophyticus (2,3).…”
Section: Introductionmentioning
confidence: 99%